Sexual Violence in Virtual World: The Unaddressed Legal Protection Issue for Victims - Syahda, Alda Widya; Ramaiah, Angayar Kanni (Neoclassical Legal Review: Journal of Law and Contemporary Issues, 2024)
Technology, the internet and social media are essential parts of our daily life. Society has become an important actor and witness to the surge in digital interactions, creating new platforms for communicating, playing games and social networking. Cyberspace's offer of creativity, connection, and entertainment turns out to have a risky side”the spread of sexual violence in digital spaces. This research argues the complex interactions between social media, adolescence, and sextortion. The study of the risks posed by online platforms and their impact on teenagers found in this research seeks to address the need for intervention in education and legal protection of the youth and vulnerable generation in the digital era. Furthermore, this paper would contribute to a safer online environment for teens and responsibility in using social media while fostering a culture of respect, consent, and awareness regarding sexual violence.